Economic evaluation of combined heat and power integrated with food waste-based ethanol production - Noor Intan Shafinas, Muhammad; Rosentrater, Kurt A. (Frontiers Media S.A., 2021)
The concern of food waste (FW) impact on the environment, societies, and economies, has triggered many researchers to find alternative ways to utilize these materials. FW can be high in glucose and other sugars (depending upon the food used) and has the potential to be converted into value-added products such as ethanol. Ethanol is an organic material that has a high demand from different industries for products such as fuel, beverages, pharmaceuticals, and other industrial applications. FW fermentation to produce ethanol may be a promising method, and might results in positive impacts on economies. However, it is a challenge for the product price to compete with that of corn ethanol due to low yield and the inconsistency of FW composition. Thus, to increase the profitability, a conventional fermentation plant integrated with a combined heat and power (CHP) system might be a great combination, and was analyzed in this study. Solid waste stream from the process can be converted into energy and could reduce the utility cost. Therefore, the main focus of this study is to evaluate the economic impact of this integrated system by estimating the minimum selling price (MSP) using techno-economic analysis (TEA) and compare to conventional plants without CHP. Results from this analysis showed that the MSE value for this integrated system was $1.88 per gallon ($0.50 per liter). This study suggests that an integrated system with CHP was found to be more economical and attractive to be implemented on a commercial scale.